2020
DOI: 10.24938/kutfd.626463
|View full text |Cite
|
Sign up to set email alerts
|

May Single One Level Intradiscal Autologous Platelet Rich Plasma Injection Play a Role in the Treatment of Discogenic Pain? Results at Six Month Follow-Up

Abstract: Objective: Low back pain is spreading both in older and younger people in a fast manner. Discogenic pain resulting from degeneration of the intervertebral disc is responsible for 40% or more of the cases of low back pain. We hypothesized that single one level intradiscal autologous platelet rich plasma (PRP) injection might provide remarkable pain relief and return to pre-illness activity level in the patients suffering from discogenic pain. Material and Methods: Twenty-two patients underwent injections of jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This suggests PRP may have potential benefits in treating discogenic pain. While some studies support the use of intradiscal PRP for discogenic pain, others have not found significant structural or functional improvement from the included studies [15 Sevgili and Sari observed remarkable pain relief and improved return to pre-illness activity levels with singlelevel intradiscal PRP injections for discogenic pain [17]. However, Akeda et al underscored the necessity for largerscale studies to validate the clinical evidence for PRP in treating discogenic lower back pain [16•].…”
Section: Supporting and Conflicting Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests PRP may have potential benefits in treating discogenic pain. While some studies support the use of intradiscal PRP for discogenic pain, others have not found significant structural or functional improvement from the included studies [15 Sevgili and Sari observed remarkable pain relief and improved return to pre-illness activity levels with singlelevel intradiscal PRP injections for discogenic pain [17]. However, Akeda et al underscored the necessity for largerscale studies to validate the clinical evidence for PRP in treating discogenic lower back pain [16•].…”
Section: Supporting and Conflicting Investigationsmentioning
confidence: 99%
“…Jain et al conducted a prospective clinical trial and concluded that intradiscal PRP injection was effective in treating discogenic low back pain, especially when higher platelet counts were used [24]. Sevgili and Sari investigated the role of single level intradiscal autologous PRP injection in the treatment of discogenic pain and reported remarkable pain relief and improved activity levels in patients [17].…”
Section: Implementation Of Prp In Patients Suffering Vertebrogenic An...mentioning
confidence: 99%
“…One RTC study was still in the peer-review process at the time of analysis and was included as a personal communication to the author [73]. Additionally, the case series involved a total of 1759 patients, with studies focusing on intradiscal (160 patients) [34,56,[79][80][81][82][83], epidural (810 patients) [64,[84][85][86][87][88], facet injection (109 patients) [89][90][91], and lumbar muscles (171 patients) [61,92] or simultaneous application in multiple targets (509 patients) [10,[93][94][95][96][97][98][99][100]. The RCTs compared the effect of PRP with saline, steroids, contrast agent, hyaluronic acid, or ozone.…”
Section: Resultsmentioning
confidence: 99%
“…In the case series group, a total of 27 articles were found. Table 5 presents 18 papers focusing on specific targets, including the disc (n = 7) [34,56,[79][80][81][82][83], epidural space (n = 6) [64,[84][85][86][87][88], facet joint (n = 3) [89][90][91], and paravertebral muscle (n = 2) [61,92]. On the other hand, Table 6 includes nine papers that explored multitarget applications, involving the disc, facet, epidural space, and/or muscles simultaneously [10,[93][94][95][96][97][98][99][100].…”
Section: Resultsmentioning
confidence: 99%